Urea Adsorption By Activated Carbon Derived From Oil Palm Kernel Shell And Empty Fruit Bunch Fiber - Ooi, Chee Heong (2014)
The present hemodialysis treatment is expensive and seriously affects the life of a patient due to its low effectiveness and efficiency in uremic toxin removal. Thus, nanoporous materials are needed to improve the treatment. Palm kernel shell (pks) and empty fruit bunch (efb) fiber biomass from palm oil mills can be utilized to synthesize low cost nanoporous activated carbon (ac) which can be applied in artificial kidney system for urea adsorption. In this study, granular activated carbon (gac) was synthesized from pks via different carbonization temperatures and durations as well as the sulfuric acid (h2so4) treatment. Activated carbon fiber (acf) was derived from efb via the treatment with different acid impregnation ratios followed by the carbonization and co2 gas activation at 900°c.